Ecological Factors Affecting Termite Infestation And Distribution And Population Management Of Coptotermes Spp (Blattodea: Rhinotermitidae) Using Chlorfluazuron Bait - Umar, Wan Ahmad Syahir Wan (2019)
In a natural ecosystem, termites play an important role as a decomposer since termite can digest cellulose. However, termites will be considered as pests once they had exerted substancial economical damages. The subterranean termites from the genus Coptotermes spp are known as the major termite pests. Type of buildings have no significant impact on the infestation level of termites as they can infest all types of building structures as long as there is cellulose, their main source of food. In this study, type of building; flat from government premises made up of 47.4% from the total buildings sample for termite infestation followed by single house, single-storey terrace house, and double-storey terrace house. Regardless of type of buildings, termite can be found attacking some common places in the buildings. Termites prefer to attack window frames (18.9%), followed by doors (13.5%) and cabinets (13.5%). From 21 surveyed sites, there are a total of 6 genera of termites (Coptotermes, Microtermes, Hospitalitermes, Globitermes, Macrotermes and Microcerotermes) of termites which include 7 termites species (Coptotermes gestroi, Coptotermes curvignathus, Macrotermes gilvus, Microcerotermes sp, Microtermes sp, Hospitalitermes sp, and Globitermes sulphureus). In this study, the most common species found infesting building area are from the species Coptotermes gestroi and Coptotermes curvignathus. Many factors affecting the activity of termite to forage for food and each kind of species react differently towards the ecological factors.